From a Victim to a Hero: A Visual Rhetoric of Donald Trump’s Attempted Assassination - Mustaqim, Andika Hendra; Haroni, Nanang (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Former President of the United States (US) Donald Trump is the most controversial politician in the history of politics in that country because of his policies and statements. Trump is back and has the dominant political power to fight Vice President Kamala Harris in the presidential election held in November 2024. The incident of the attempted assassination of Trump on July 14th, 2024 while campaigning had many positive impacts in the midst of very strong political polarization. This research goal to explore the elements and meaning of visual rhetoric in two videos uploaded on social media about the attempt to assassinate Trump. The results of this research answer that the historical and contemporary context, formal description, nature, function and evolution of image indicate that the attempted assassination was a political consequence of a leader fighting in democracy. The most important meaning is Trump's effort to construct himself from a victim to become a hero through his performance to show unity and nationalism